Plasticity of gamma delta T cells: impact on the anti-tumor response - Lafont, Virginie; Sanchez, Françoise; Laprevotte, Emilie; Michaud, Henri-Alexandre; Gros, Laurent; Eliaou, Jean-François; Bonnefoy, Nathalie (Frontiers in Immunology, 2014)
The tumor immune microenvironment contributes to tumor initiation, progression, and response to therapy. Among the immune cell subsets that play a role in the tumor microenvironment, innate-like T cells that express T cell receptors composed of γ and δ chains (γδ T cells) are of particular interest. γδ T cells can contribute to the immune response against many tumor types (lymphoma, myeloma, melanoma, breast, colon, lung, ovary, and prostate cancer) directly through their cytotoxic activity and indirectly by stimulating or regulating the biological functions of other cell types required for the initiation and establishment of the anti-tumor immune response, such as dendritic cells and cytotoxic CD8+ T cells. However, the notion that tumor-infiltrating γδ T cells are a good prognostic marker in cancer was recently challenged by studies showing that the presence of these cells in the tumor microenvironment was associated with poor prognosis in both breast and colon cancer. These findings suggest that γδ T cells may also display pro-tumor activities. Indeed, breast tumor-infiltrating γδ T cells could exert an immunosuppressive activity by negatively regulating dendritic cell maturation. Furthermore, recent studies demonstrated that signals from the microenvironment, particularly cytokines, can confer some plasticity to γδ T cells and promote their differentiation into γδ T cells with regulatory functions. This review focuses on the current knowledge on the functional plasticity of γδ T cells and its effect on their anti-tumor activities. It also discusses the putative mechanisms underlying γδ T cell expansion, differentiation, and recruitment in the tumor microenvironment.